Empowering farmers through front line demonstrations on the management of shoot and fruit borer (Leucinodes orbonalis Guenee) in brinjal (Indian Journal of Arid Horticulture, 2025)
This study assessed the efficacy of emamectin benzoate 5 SG (0.0025%) in managing the shoot and fruit borer of brinjal through front line demonstrations (FLDs) conducted during 2021-22, 2022-23, and 2023-24 in Kalol Taluka and Panchmahal districts of Gujarat. The study compared demonstrated practice (emamectin benzoate 5 SG @ 12.5 g a.i./ ha) with farmer’s practice (inconsistent pesticide use). Results revealed significant reduction in pest damage under the recommended practice, with shoot borer infestation decreasing from 7.25% to 8.50% and fruit borer damage reducing from 13.50% to 15.50%, compared to 17.50%-18.75% and 22.75%-23.50%,  respectively, under farmer’s practice. Yield increased from 235.25 q/ ha (2021-22) to 249.75 q/ ha (2023-24) in the recommended practice, significantly higher than farmer’s practice yields (170.50 to 198.50 q/ ha). The technology gap was 45.83 q/ ha, extension gap 55.75 q/ha, and technology index 16.37%. Economic analysis showed a B:C ratio of 3.10 for the recommended practice versus 2.56 in farmer’s practice, with an additional net return of ₹ 28,400/ ha. The study confirms that emamectin benzoate 5 SG effectively manages brinjal fruit and shoot borer, enhancing productivity and profitability, making it a viable pest control strategy for sustainable brinjal cultivation.